Yeast tRNA precursor mutated at a splice junction is correctly processed in vivo. - Colby, D (1981)
Yeast mutants with decreased expression of a tRNATyr gene were obtained by selection for functional inactivation of the tyrosine-inserting ochre suppressor SUP4 and subsequent screening for production of the tRNA gene product in vivo. One mutant with reduced suppressor activity was characterized by a decreased quantity of the suppressor-specific tRNA; a precursor to this tRNA, matured at both 5' and 3' termini but still containing a 14-nucleotide intervening sequence, was present in an amount greater than 7-fold that in the parent. By RNA sequence analysis of the accumulated precursor, we have identified the mutation as an A leads to G transition at the 5' splice junction. Similar analysis of the mature tRNA produced in this mutant demonstrated that the intervening sequence was accurately excised. We conclude that the specific sequence of nucleotides at this splice junction affects the efficiency but not the fidelity of processing.